PERKEMBANGAN INDUSTRI TENUN ULOS DI KELURAHAN SIGULANG-GULANG, KECAMATAN SIANTAR UTARA DAN PENGARUHNYA TERHADAP SOSIAL EKONOMI MASYARAKAT TAHUN 1998-2005 - Nainggolan, Evan (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2014)
This study aims to determine : 1) Introduction emergence of industry weaving ulos in the village of Sigulang-gulang 2) the development of industry weaving ulos in the village of Sigulang-gulang 3) influence of industry weaving ulos for social economic society in the village of Sigulang-gulang. The method used in this paper is the method of historical research , because this research is related to the fact that occurred during the study lampau.Berdasarkan obtained the following results :Influence industry weaving ulos to a life social economic and a impact very feel for the people of village Sigulang-gulang. Increasing the quality of education, the emergence of new field jobs and press the amount of unemployment for the community around and immigrants, increasing the income of the community, increase the number of new entrepreneurs. Â